User Interface Design With User Centered Design (UCD) Method on Bread Sales Mobile Application PT.Nippon Indosari Corpindo, Tbk. - Az-zahra, Salsa; Jaelani, Irsan; Sri Andar Muni, Lise (RISTEC : Research in Information Systems and Technology, 2021)
PT. Nippon Indosari Corpindo,Tbk. is one of the companies engaged in the food industry with its flagship product, namely bread with the brand